(untitled) (Encuentros, 2023)
It is proposed an experimental task with the Kogi ancestral wise men, including those who are Mamas (knowledgeable men), translators and teachers. With the answers to the moral dilemmas, it is possible to demonstrate, in the first place, that the Kogi indigenous usually base their moral judgements on a cognitive process whose objective is to identify and reject harm. In the second place, it is verified that the given indication is fulfilled for Mamas as well as otherwise men that do not hold such quality (translators and teachers). In the third place, it is shown that indigenous people reject harm no matter the possible victims’ quality, it means, independently if it is a non-indigenous person (or that does not belong to the group), a Kogi indigenous person (that belongs to the group), or Nature (conceived in the Kogi worldview as a living being object of cult). These indications seem to propose Kogi wise men as an exceptional case faced to prescriptions of the dual model. Finally, the study shows that the experiment results could also allow to point out ways to clarify cultural concepts.